The Use Of A Modified Strategy-Based Module In Developing Creative Thinking And Self-Concept Of Low Achievers In Jordan - Al-Badareen, Shadi Khaled Abdullah (2013)
The purpose of this study was to find the effectiveness of a modified strategy-based module (MSBM) that based on CoRt and SCAMPER in the development of creative thinking and self-concept among a sample of low achievers in Jordan. The study sample comprised 160, sixth year female and male elementary low achievers randomly selected from 8 resource rooms at Al-mafareq governorate. The sample was divided into four groups. The experimental groups received the modified strategy-based module (MSBM) and the control groups received the currently strategy-based used module (CSBUM) for four weeks, after which a post-test was administered. The findings revealed that there is a significant difference between the post-test means of the two experimental groups against the two control groups’ performance. An analyses of variance based on correct responses recall for the (Piers-Harris 2 Self –Concept Scale) and (Torrance Creative Thinking Test) posttests’ grades indicated significant differences between the experimental and control groups in their creative thinking and self-concept. In summary, the findings of this study not only support current opinion regarding the state of training low achievers’ creative thinking and self-concept in Jordan, but more pertinently, it highlights the fact that remedial action needs to be taken to address the inherent failure of the educationists to follow effective methods to improve low achievers’ creative thinking and self-concept to improve academic performance. One way of doing so would be to use the findings of this study to look into the possibility of training low achievers in the Jordanian resource rooms in a useful and integrative manner. Consequently, the study has recommended some suggestions.